ONOMATOPE DALAM BAHASA MAKASSAR (Onomatopoeia in Makassarese Language) - Nursiah Tupa (SAWERIGADING, 2015)
This study aims to describe onomatopoeia Makassarese language. Onomatopoeia are words that are created by imitation sound from nature or the sound produced by certain objects. Even onomatopoeic words that are not exactly the same as the imitated sound, but opinion from language speaker, lexicon is an imitation sound. The method used is descriptive with notes, classification, and observation techniques. Data was collected by recording sounds similar to the imitated objects. In data processing, first of all the data is classified basedon the form and type of sound that imitated. Referring to the technique, it is done by listening to sounds and then matching it to the shape of the sound in accordance with objects or animals that produced the sound. The results from data analysis found that onomatopoeia or imitation sounds in Makassarese language can be classified based on animal sounds, sound objects, sound natural phenomena, sound produced by actions, processes, events, or circumstances.